Website Security Analysis of SIDESPIN Application Using Vulnerability Scanning Techniques - Rasmila Rasmila; Rafi Herawan (LPPM Universitas Islam 45 Bekasi, 2024)
In the era of globalization, quick and easy access to information is essential, especially through the Internet. Websites have become one of the main media for delivering information globally. Although it provided extensive benefits, the use of websites also brings security risks. Errors in coding and configuration can lead to vulnerabilities that can be exploited by irresponsible parties. This research aims to conduct a security analysis on the SIDESPIN website, owned by the Directorate of Innovation and Business Incubator of Bina Darma University. By applying vulnerability scanning techniques, this research identifies vulnerabilities, analyzes findings, and provides recommendations for improvement. In stages such as scoping, footprinting, vulnerability scanning, vulnerability analysis, and reporting, this research uses tools such as OWASP ZAP, Nikto, and Nessus. The result is a vulnerability analysis along with recommendations that can serve as guidelines to improve the security of the SIDESPIN website